Coefficient of correlation between pH and alkalinity of sangmeshwar reservoir in osmanabad district, Maharshtra, India - Jadhav, Dilip; Shinde, Sandhya; Mane, A S (International Multidisciplinary Research Journal, 2011)
The present study attempts to bring an acute awareness among the people about the quality of ground water by taking water samples from specific locations for analysis. During present investigation an attempt has been made to study the physico chemical properties of Sangmeshwar reservoir, Osmanabad district of Maharashtra State, India. In this paper an attempt has been made to correlate the pH and alkalinity of reservoir water.